GROWTH AND YIELD OF SHALLOT LEMBAH PALU VARIETY ON DIFFERENT DIRECTION AND FORM OF SEEDBEDS GROWING ON DRY LAND - Muhammad Anshar; Imam Wahyudi; Bahrudin Bahrudin (AGROLAND: The Agricultural Sciences Journal, 2016)
This study aimed to determine the growth and yield of shallot Lembah Palu variety planted on dry land with different direction and form of seedbeds. It have been carried out in January-April 2013 in the village of Guntarano, Tanantovea Sub Districts, District of Donggala, Central Sulawesi. This study used a Spilt Plot Design. The main plot was the seedbed direction (A) consisting of: (A1) = seedbeds in the direction of the slope of the land, and (A2) = seedbeds crossed  the slope direction. Sub-plot was the form of beds (B) comprises of: (B1) = depth seedbeds and (B2) = high seedbeds. Each treatment was repeated 3 times, so that there were 12 experimental units.  The research found that (i) the direction of the beds as well as its interaction with the form of beds did not significantly affect the growth and yield of shallot ‘Lembah Palu’ on dry land. (ii)   depth seedbeds produces the number of leaves, leaf length, leaf dry weight, total leaf areaper plant, and total dry weight per plant, and the number of tubers per clump and the weight of the harvested dry tuber per hectare was higher than high seedbeds form.